2015
DOI: 10.1200/jco.2014.57.1414
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Mutations in 17 Breast Cancer Susceptibility Genes Among a Large Triple-Negative Breast Cancer Cohort Unselected for Family History of Breast Cancer

Abstract: Deleterious mutations in predisposition genes are present at high frequency in patients with TNBC unselected for family history of cancer. Mutation prevalence estimates suggest that patients with TNBC, regardless of age at diagnosis or family history of cancer, should be considered for germline genetic testing of BRCA1 and BRCA2. Although mutations in other predisposition genes are observed among patients with TNBC, better cancer risk estimates are needed before these mutations are used for clinical risk asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
426
8
49

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(533 citation statements)
references
References 42 publications
43
426
8
49
Order By: Relevance
“…Mutations in the BRIP1 gene seem to be more frequent in women with early-onset BC and triple-negative BC 108 . About 1% of patients with early-onset or familial BC carry a deleterious mutation 103 .…”
Section: Brip1mentioning
confidence: 99%
“…Mutations in the BRIP1 gene seem to be more frequent in women with early-onset BC and triple-negative BC 108 . About 1% of patients with early-onset or familial BC carry a deleterious mutation 103 .…”
Section: Brip1mentioning
confidence: 99%
“…In women testing negative for BRCA1 and BRCA2 mutations, multi-gene germline sequencing identifies up to another 10% of patients with pathogenic mutations [21]. Recently, a large study of multi-gene germline testing in over 1,800 unselected patients with TNBC demonstrated that overall mutation rate was 14.6% with 8.5% having mutations in BRCA1, 2.7% in BRCA2 and an additional 3.7% with mutations in other genes such as PALB2 (1.2%), BRIP1, BARD1, and RAD51C among others [22]. Cancers arising in these genetic backgrounds are hypothesized to have HR DNA repair defects and therefore may have similar chemosensitivity to DNA-damaging therapies as BRCA1/2 mutation carriers [4,23].…”
Section: Germline Hr Pathway Mutations Beyond Brca1 and Brca2 As Hr Dmentioning
confidence: 99%
“…One study was excluded from this review despite the high number of patients, because the authors chose to study only 36 known pathogenic mutations in the selected HBOC genes [14]. The highest number of patients included was 10030, most of whom had HBOC, although one study was limited to unselected TNBC patient [31] and another one to OC [29]. Two studies included exclusively patients previously tested negatively for BRCA1/2 mutations [25,27].…”
Section: Discussionmentioning
confidence: 99%